(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2012)
Verrucous carcinoma is a well differentiated papillary squamous cell carcinoma that may invade locally bu rarely metastasizes. A 65 years old farmer presented with a huge ugly looking verrucous carcinoma on left angle of mouth involving cheek and zygoma at Chittagong Medical College Hospital in July 2010. Clinical examination and CT scan revealed neither bony nor regional lymph node involvement. The enormous growth was excised and reconstructed by Radial Forearm Free Flap. Standard microvascular techniques were followed. Patiend had uneventful postoperative recovery. Radial forearm free flap was taken & well matched with the facial tissue leaving no donor site morbidity. Follow up was done monthly for the first 6 months and 3 monthly onward. No recurrence is noticed yet, even after 18 months. JCMCTA 2011; 22(2): 50-52